Career Preference of Business Graduate in Bangladesh: A Case Study of Some Selected Private Universities - Hossain, Mohammad Emdad; Siddique, Tabassum (Asian Business Review, 2012)
This paper attempts to investigate the career preference of business graduates of private universities in Bangladesh. A total number of 256 final year business students, irrespective of gender in 15 private universities located in Dhaka city have been interviewed. Majority of the respondents’ preferred field for future career development are banks and multinational companies. More than average of the total respondents plans to seek employment in their chosen field specially after obtaining the bachelor's degree. The major business courses that have been chosen by the business undergraduate students for specialization are finance and banking, human resource management, accounting and marketing. Financial benefit and social status were the major motivations for the business graduates’ career preference. In case of major reasons of motivation, the male respondents are highly influenced by the financial benefit, social status and good opportunities in the chosen field. On the other hand, the female respondents identified financial benefit, social status and job security as their most influencing reasons behind career preference.